Standardized pre-procedural clinical workup for protected percutaneous coronary intervention. (8th December 2022) - Al-Rashid, Fadi; Van Mieghem, Nicolas M; Bonello, Laurent; Oreglia, Jacopo; Romagnoli, Enrico
Abstract: In addition to appropriate patient screening, pre-procedural preparation is essential to optimize both technical success and patient outcome for protected percutaneous coronary intervention (PCI). A critical component of optimization is the identification and preparation of a suitable femoral access site. Here, we describe several options for both imaging and image-guided access to optimize the approach.